(untitled) (CIPEEX, 2025)
Oxidative stress accelerates cellular aging by damaging essential cell structures. This summary aims to describe the mechanisms and impacts of oxidative stress on cellular aging. This is a narrative literature review conducted through searches in the PubMed and SciELO databases. Articles published in the last five years that addressed the proposed topic were included, excluding those that did not meet the established criteria. There are several sources of free radicals, such as normal cellular metabolism, UV radiation, smoking, and poor diet. When free radicals are in excess and are not neutralized, they damage essential cell components such as lipids, proteins, and DNA. Lipid peroxidation generates toxic aldehydes, while proteins undergo modifications that compromise their functions. ROS can damage DNA, causing mutations and base modifications that disrupt genetic information and integrity. By attacking the DNA base guanine, oxidative stress directly damages telomeres and accelerates shortening, contributing to aging. An excess of these substances causes mitochondrial dysfunction, cellular senescence, and chronic inflammation (SASP). Excess ROS compromises mitochondrial function, damaging structures, which reduces energy production and promotes cellular senescence. At the same time, an imbalance in the gut microbiota intensifies oxidative stress and promotes low-grade chronic inflammation, in addition to increasing intestinal permeability and the translocation of endotoxins into the circulation. The body uses antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) to neutralize reactive oxygen species. Molecules such as glutathione, vitamins C and E, and polyphenols also act as barriers against oxidative damage. These mechanisms preserve lipids, proteins, and DNA, slowing cellular aging and pointing to the importance of therapeutic strategies involving antioxidant substances.